Raising Tax Revenue : How to Get More from Tax Administrations? - Chang, Eui Soon (IMF Working Papers; Working Paper, 2020)
Can we empirically show the benefits of improving the practices and characteristics of tax administration agencies for revenue collection? While many country experiences suggest a strong link, there is little systematic empirical evidence on the matter. This paper analyzes the association between tax collections and tax administrations, using the novel dataset (ISORA). We find that tax performance is positively and strongly associated with the operational strength of tax administrations. Among emerging and low-income economies, countries at the top 25 percent (in terms of the operational strength) collect substantially larger tax revenues (by 3u percent of GDP) than countries at the lowest 25 percent, assuming other conditions are equal. Our results also suggest that adopting key administrative practices such as compliance risk management and use of third-party data is associated with stronger tax collections. Furthermore, larger staffing of a tax agency improves tax revenue up to a point. These findings have important policy implications, particularly during the unprecedented global pandemic situation.